Inteligentne systemy wspomagania decyzji marketingowych w przedsiębiorstwie - Kałążna-Drewińska, Urszula (Functioning of the Intelligent Systems as Marketing Decision Helpers in Business, 2006)
As a result of the evolution of SIM (System of Marketing Information) the systems called "Marketing Decision Helpers" (SWDMs) came into existence. Expert systems based on the artificial intelligence are an example of Marketing Decision Helper systems. Currently even more advanced information systems, which are used in marketing management, are being developed. They include: knowledge based marketing systems, marketing systems based on occurrence by chance, marketing "neuron nets", programs supporting creativity
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Marketing (2); 2006; nr 1110, s. 60-69